A construção das personagens em “Amor, plástico e barulho” : uma análise a partir da teoria decolonial - Aquino, Fernanda Ribeiro de (2021)
This paper reviews “Amor, Plástico e Barulho” (Brazil/2013) construction of the characters in the film, a work by the Pernambuco director Renata Pinheiro, in which a methodological inspiration called screen ethnography has been carried out. The objective of the research focuses on analyzing the construction of characters from the perspective of decolonial feminism, pointing out resemblances between the characters experiences and those of peripheral female singers, highlighting on the specific way in which oppressive relationships are established in a musical environment in which is mostly male, an aspect that is reinforced through the evaluation between my experiences and my sister, since we are professional singers belonging to different sectors (author music and electronic forró, respectively). To conclude, this paper concentrates its results in an important point of view of decolonial debate for society, for the academy, and in the case of the research, to encourage women artists, black, peripheral, to take up and somewhat resist